2017
DOI: 10.1002/pnp.457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of cognitive screeners in older people

Abstract: Age is a key risk factor for cognitive impairment and dementia, although cognitive complaints may also occur in younger people. Here, the authors re‐analyse data from several pragmatic diagnostic test accuracy studies examining various short cognitive screening instruments (CSIs) in a secondary‐care, neurology‐led, cognitive disorders clinic and establish whether any CSI tests are more favourable in the older age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…The findings confirmed those of the preliminary report, (11) and greatly extended these, by examining two MACE cut-offs, two age cut-offs, and more summary measures in a larger patient cohort. The results suggest that in clinical practice either MACE cut-off may be chosen, dependent upon exact clinician requirements, since both increase PPV.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings confirmed those of the preliminary report, (11) and greatly extended these, by examining two MACE cut-offs, two age cut-offs, and more summary measures in a larger patient cohort. The results suggest that in clinical practice either MACE cut-off may be chosen, dependent upon exact clinician requirements, since both increase PPV.…”
Section: Discussionsupporting
confidence: 85%
“…Some preliminary (two-year) data from this study have appeared as part of a broader study examining the utility of various CSIs in older patients (aged ≥ 65 years) seen in a dedicated cognitive disorders clinic. (11)…”
Section: Mini-addenbrooke's Cognitive Examination (Mace): a Useful Cognitive Screening Instrument In Older People?mentioning
confidence: 99%
“…Generalization of the current findings to other settings may not therefore be possible, although an examination in an older patient subgroup from this clinic showed better metrics for MACE than in the sample as a whole [13]. The absence of data on education precluded examination of its effect on MACE performance.…”
Section: Discussionmentioning
confidence: 96%
“…In a nephrology clinic cohort of patients with chronic kidney disease and diabetes (n = 112), the sensitivity and specificity for a dementia diagnosis were 0.96 and 0.84, respectively, at the cut point < 25/30 [6]. Studies in a dedicated cognitive disorders clinic have suggested superiority of the MACE to MMSE [7][8][9] and single-item cognitive screening questions [10] and equivalence to the Montreal Cognitive Assessment (MoCA) [9,11,12], and a better performance in those aged > 65 years, with a higher prevalence of cognitive impairment [13]. In a study of patients with mild AD (n = 92) and healthy controls (n = 68), MACE had an area under the receiver operating characteristic (AUC ROC) curve of 0.939, which was superior to ACE-III (0.897), Rowland Universal Dementia Assessment Scale (0.889), MMSE (0.874), Memory Impairment Screen (0.866), and MoCA (0.856) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study replicate prior findings demonstrating the utility of the MoCA total score as an initial screen for MCI and AD. [1, 1114] The total score had large effect sizes, and these values increased in distinguishing MCI vs. Cognitively Normal (d=0.83), AD vs. MCI (d=1.60), and AD vs. Cognitively Normal (d=2.38) groups. The large effect sizes in the current study, based on a research sample screened for MCI and AD, replicates the findings in clinic samples.…”
Section: Discussionmentioning
confidence: 99%